Fusion technology 1988 : proceedings of the 15th Symposium on Fusion Technology, Utrecht, the Netherlands, 19-23 September 1988 - Ingen, A. M. van (Adrianus Marinus van), 1932-; Nijsen-Vis, A. (Adriana), 1938-; Klippel, H. T. (Hendrik Theodorus), 1939- (North-Holland ; Sole distributors for the USA and Canada, Elsevier Science Pub. Co., 1989)
Invited Papers Repr. from Fusion Engineering and Design, Vol. 11, Nos. 1 &.